Analisis Penerapan Metode Bi Al-Ma'sur Dalam tafsir Ibnu Katsir Terhadap Penafsiran Ayat-Ayat Hukum - Nurdin Nurdin (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2013)
afs?r al-Qur?n al-A??man exegete Ibn Kathirs work. Feature is that the sharpness of analysis in reviewing the problems associated with the interpretation of the verses of the Koran. Differences of opinion are clearly presented, and then criticized the arguments put forward strong and defensible. The language is very easy to understand. Ibn Kathir using bi al-matsur. he was very careful and did not stick to the liberal and verses of the Koran, hadith, atsar friend and opinions of the scholars of the Salaf. But it looks less consistency in the interpretation of the piece QS al-Isr?: 78 of the Asr prayer and evening prayer time. Determine both prayer time, he was not based on history or the opinion or tabiin Companions (as one method of bi al-matsur). He interprets the verse pieces with al-rayi (ratio). Did Ibn Kathir consistently apply the method of bi al-matsurin the interpretation of legal texts? Based on the study, interpretation of Ibn Kathir in the verses of the law, never out of frame jumhur, and he always rejects the notion that outside Sunni or Ahlus Sunnah.